2018
DOI: 10.1142/s100538671800010x
|View full text |Cite
|
Sign up to set email alerts
|

On Generalized Non-commuting Graph of a Finite Ring

Abstract: The non-commuting graph Γ R of a finite ring R with center Z(R) is a simple undirected graph whose vertex set is R \ Z(R) and two distinct vertices a and b are adjacent if and only if ab = ba. In this paper, we show that Γ R is not isomorphic to certain graphs of any finite non-commutative ring R. Some connections between Γ R and commuting probability of R are also obtained. Further, it is shown that the non-commuting graphs of two Z-isoclinic rings are isomorphic if the centers of the rings have same order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Recently, Buckley, MacHale and Ní Shé [2] have introduced Zisoclinism between two rings and showed that the commuting probabilities of two Zisoclinic finite rings are same. Dutta, Basnet and Nath have generalized the concept of Z-isoclinism between two rings in Definition 5.1 of [6]. Note that Definition 5.1 of [6] can be generalized in the following way.…”
Section: Isoclinism and Commuting Probabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Buckley, MacHale and Ní Shé [2] have introduced Zisoclinism between two rings and showed that the commuting probabilities of two Zisoclinic finite rings are same. Dutta, Basnet and Nath have generalized the concept of Z-isoclinism between two rings in Definition 5.1 of [6]. Note that Definition 5.1 of [6] can be generalized in the following way.…”
Section: Isoclinism and Commuting Probabilitymentioning
confidence: 99%
“…Dutta, Basnet and Nath have generalized the concept of Z-isoclinism between two rings in Definition 5.1 of [6]. Note that Definition 5.1 of [6] can be generalized in the following way. Definition 4.1.…”
Section: Isoclinism and Commuting Probabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, |Y | = |X 1 ||X 2 | and hence the result follows. Now we deduce a relation between Pr r (R) and the number of edges in the r-noncommuting graph of R. The r-noncommuting graph of a finite ring R, denoted by Γ r R , was introduced and studied in [6]. Recall that Γ r R is a graph whose vertex set is R and two distinct vertices x and y are adjacent if [x, y] = r and [y, x] = r. Let E(Γ r R ) denote the set of edges of the graph Γ r R .…”
Section: Introductionmentioning
confidence: 99%